The Characteristic Function of a Neutrosophic Set - A. A. Salama; Florentin Smarandache; S. A. Alblowi (Neutrosophic Sets and Systems, 2014)
The purpose of this paper is to introduce and study the characteristic function of a neutrosophic set. After given the fundamental definitions of neutrosophic set operations generated by the characteristic function of a neutrosophic set ( Ng for short), we obtain several properties, and discussed the relationship between neutrosophic sets generated by Ng and others. Finally, we introduce the neutrosophic topological spaces generated by Ng. Possible application to GIS topology rules are touched upon.